Physical and recreational activity in the life of institutionalized elderly people: Why reflect contemporary multidimensionality? (Research, Society and Development, 2025)
The objective is to identify the impact of recreational and physical activities on the quality of life of institutionalized elderly individuals, highlighting the importance of such practices in promoting active aging and preserving autonomy in contemporary geriatrics at the national level. This is a descriptive, exploratory, and qualitative study conducted through an integrative literature review. The search for studies was carried out in the Virtual Health Library (BVS) database, focusing on publications from 2020 to 2024. In the final selection phase, all manuscripts were read in full, resulting in a final sample composed of 15 complete scientific texts. The analyzed studies demonstrate that regular physical and recreational activity provides various health benefits to the elderly, including improved cardiorespiratory fitness, muscle strengthening, increased joint mobility, better balance, fall prevention, and cognitive enhancement. Additionally, there is a positive impact on self-esteem, social relationships, and the reduction of depression and isolation. The strategic role of transdisciplinary professionals as health promoters in long-term care institutions is also emphasized. Interdisciplinary collaboration among health specialties is essential to ensure active and dignified aging. Recreational activities are indispensable allies in the process of healthy aging. Their inclusion in public policies and in institutions serving the elderly population should be strengthened to promote comprehensive health. Valuing the elderly as active subjects of their own stories, along with the provision of accessible physical practices, significantly contributes to quality of life.